Zimbabwe : First Review of the Staff-Monitored Program; Staff Report; and Press Release. (IMF Staff Country Reports; Country Report ;, 2015)
EXECUTIVE SUMMARY Context. The Zimbabwean authorities have made progress in implementing their macroeconomic and structural reform programs, despite the economic and financial difficulties. During 2015, the authorities' policy reform agenda will continue to focus on: (a) reducing the primary fiscal deficit to raise Zimbabwe's capacity to repay; (b) restoring confidence in the financial system; (c) improving the business climate; and (d) garnering support for an arrears clearance strategy. Recent developments, outlook, and risks. Zimbabwe's economic prospects remain difficult. Growth has slowed and is expected to weaken further in 2015. Despite the favorable impact of lower oil prices, the external position remains precarious and the country is in debt distress. Key risks to the outlook stem largely from a further decline in global commodity prices, fiscal challenges, and possible difficulties in policy implementation. However, the authorities are committed to intensifying their efforts to ensure successful implementation of the program and to lay the ground for stronger, more inclusive, and lasting economic growth. Program performance. All quantitative targets and structural benchmarks for the first review under the staff-monitored program (SMP) were met. The authorities demonstrated strong commitment to the program, in a difficult economic and financial environment. Moreover, they have made meaningful progress in implementing other key structural reforms, such as making operational an asset management company and amending the indigenization and empowerment law. Reengagement with creditors. The authorities have stepped up their reengagement with creditors, including by increasing payments to the World Bank (WB) and the African Development Bank (AfDB), a key step in their roadmap toward seeking rescheduling of bilateral official debt under the umbrella of the Paris Club. These developments constitute important steps toward reengaging with the international financial institutions (IFIs). They plan to step up their efforts to build consensus among creditors and development partners on ways to address the external arrears.